Autologous stem cell transplantation in multiple myeloma at Chris Hani Baragwanath Academic Hospital - Vedanand Rawoo; Moosa Patel; Atul B. Lakha; Vinitha Philip; Muhammed F. Waja (South African Journal of Oncology)
Background: Autologous stem cell transplantation (ASCT) is the standard of care for multiple myeloma (MM), even in the era of novel therapeutic agents. Data regarding ASCT outcomes in MM is lacking in South Africa.